Clinicopathology & Molecular Analysis of Diffuse Intrinsic Pontine Glioma (DIPG) in Children - Insights from Past, Present, and Future Directions - Biswas, Arupam (Journal for Research in Applied Sciences and Biotechnology, 2022)
Diffuse Intrinsic Pontine Glioma, or DIPG, is a rare, highly aggressive, heterogeneous group of brainstem tumors. Around 10-20% of primary brain tumors are considered pediatric brain tumors, of which 10-15% are diffuse brainstem tumors. It is considered untreatable and surgically unremovable due to its intrinsic position within the brain. Over the years, applying radiotherapy and chemotherapy has not shown a better outcome. However, gene-targeted therapy has proven successful, but it is still in the developing phase. This article covers the various aspects of DIPG, from clinical and molecular definitions to a vision for a universally accepted novel approach to beat this severe condition by joining fundamental science and translational research.